'Never Again': Transitional Justice and Persistent Police Violence in Argentina. (6th May 2014) - Bonner, Michelle D.
Abstract 1 : On 31 January 2009, 16-year-old Luciano Arruga disappeared. His case is not an isolated one: more than 213 people were 'disappeared' by security forces in Argentina between 1983 and 2012. Certainly, these numbers pale in comparison to what occurred during the last dictatorship, when as many as 30, 000 people disappeared. Yet, Argentina has pursued many transitional justice processes to address this past with the goal of nonrepetition or, as the truth commission put it, 'Never Again' ( Nunca Más ). Drawing on interviews as well as media and document analysis, this article analyzes the discursive obstacles faced by actors of social accountability – the media and human rights organizations – when applying lessons from the past to current police violence. I argue that the complex relationship between human rights and security is at the heart of this discursive challenge.1